KY (Kiken Yochi=predict hazard) in working habit; assessment of its implementation way and effectiveness in manufacturing factory / Mohd Isham Ismail - Mohd Isham , Ismail (2018)
This research aims to know and analyze the application training of Occupational Health and Safety (OHS), focus on Kiken Yochi Training at a car manufacturing plant located at Serendah, Selangor. “Kiken Yochi” or KY is an act of predicting danger that is one of the key elements of safety. The study was conducted using research descriptive method that gives an overview of the programming of Kiken Yochi Training at Company A Manufacturing Sdn Bhd (Company A). Data obtained from direct observation to the field, conducting interviews to related parties and then do literary studies comparing data with prevailing laws and theories. As a prevention effort of work accident at Company A, Kiken Yochi Training Program is one of the activities being done for improving the hazard identification and risk assessment skills, so that workers can identify the dangers existing around workplace and then taking the correct measures. In order to be able achieving the effectiveness and efficiency in Kiken Yochi Training, several processes being implemented, i.e. identification of training needs, training program planning, development of training programs and evaluation of training programs. Results of the assessment on the implementation of KY activities, it has concluded to have achieved the target and objectives but there are still having room for improvement, and recommendation measures have been proposed. Keywords: Kiken Yochi Training, KY, Hazard, Risk Assessment